Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak dalam Membayar PBB dengan Variabel Moderating Sikap Wajib Pajak atas Sanksi Denda (Studi Empiris Pada Wajib Pajak Orang Pribadi Dikota Tidore Kepulauan) - -, Hasannudin (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2014)
Taxation is a source of enormous revenue contribution in the financing needs of government spending and national development. UN entry of urban and rural areas in 2010 as a local tax, assessed will contribute significantly to the increase in revenue (PAD). Tidore Tidore island is one of the autonomous regions that have natural resources and a limited area, so that the UN considered to be very potent in increasing revenue Tidore islands, because it has an advantage in this regard, is the object of the UN, the land and buildings that are clear designation compared with other tax potential. Data obtained from DISPENDA Tidore islands associated with the acceptance of the United Nations rural and urban, showed that there is still a sizeable UN arrears of revenue realization of the United Nations, especially in 2012 that showed a significant difference between actual revenue in the amount of 77,878,186 principal. and arrears amounting to 568 826 671. it indicates that there are a number of factors that influence taxpayer compliance in paying UN Tidore islands in the city. The purpose of this study was to determine the factors that influence taxpayer compliance in paying UN moderated attitude taxpayer on the implementation of financial penalties. The method used in this study was a multiple linear regression. Research results showed that awareness of the taxpayer, the taxpayer's motivation, and economic level of each taxpayer partially no effect on taxpayer compliance in paying the UN, and each of which is moderated by the attitude of the taxpayer on the implementation of financial penalties. Where the taxpayer stance on the implementation of financial penalties is not a moderating variable, melaikan independent variables. While the partial attitude of the taxpayer on the implementation of fines effect on taxpayer compliance in paying the UN. it shows that the revenue department Tidore islands has a poor performance and not optimal in managing urban and rural United Nations.